Poland syndrome: Atypical presentation and review of literature - Mittal, Hema Gupta; Singh, Yashvant; Tatawat, Hemant; Maria, Arti (Indian Journal of Child Health, 2022)
Poland syndrome is a rare congenital disorder with absent or hypoplastic pectoralis major and hand anomalies. Dextroposition, female predisposition, and the left-sided anomalies in Poland syndrome are rarely reported in literature. We report a female baby who was born with chest wall defects, left hand anomalies, dextroposed heart, and hypoplastic ribs. She was diagnosed as Poland syndrome and managed conservatively.